Body- Building e a confiança e medo no uso dos esteroides anabolizantes: uma análise sociológica - Silva, Fabiano Almeida da (2012)
This paper discusses the problem of the intensive use of anabolic-androgenic steroid hormones (AAS), also popularly known as anabolic steroids by male gym-goers in a popular neighborhood in the city of João Pessoa. This research aims to understand, within a sociological perspective, the relationship of confidence and fear in the uses of anabolic steroid hormones, as well as their own motivations for the practice of bodybuilding and the use of these drugs masculinizing. Given the above, it is clear that in contemporary society, the body became a central element in the lives of many individuals, this reality, the result of the phenomenon of the cult of the body that in recent decades took radicalized forms. In this context, while the corpolatria intensifies, paradoxically grows in the same proportions, the people's dissatisfaction with their body image, especially when compared to ideal body widely socially valued. This situation is aggravated in a society in which we are charged, tried, identified and classified by body image. Thus, the overestimation of body image is causing many people to commit excesses in the use of many different ways in the pursuit of body aesthetically "perfect." These excesses are increasingly "blind", a symptom of the culture of presenteeism, which maintains the "now" as most important time for those seeking the transformation of body shape. These phenomena affect many individuals to embark in the underworld of the use of anabolic steroids with intent to build a body "healed" in a short time. In these circumstances the trust and fear is particularly important, because from these two elements, individuals direct their actions and speeches for use or not use of these substances.